Carbon and hydrogen stable isotope analysis for characterizing the chemical degradation of tributyl phosphate. (December 2018) - Liu, Jia; Wu, Langping; Kümmel, Steffen; Yao, Jun; Schaefer, Thomas; Herrmann, Hartmut; Richnow, Hans-Hermann
Abstract: Tributyl phosphate (TBP) belongs to the group of trialkyl substituted organophosphate esters. Its chemical reactivity depends on the stability of various chemical bonds. TBP was used as a model compound for the development of a concept using stable isotope fractionation associated with bond cleavage reactions for better understanding the fate of TBP in the environment. Carbon isotope enrichment factors (εC ) of TBP hydrolysis were found to be pH dependent (−3.8 ± 0.3‰ at pH 2, -4.6 ± 0.5‰ at pH 7, -2.8 ± 0.1‰ at pH 9, no isotope fractionation at pH 12), which is in accordance with the mode of a SN 2 hydrolytic bond cleavage. Hydrogen isotope fractionation was negligible as no H bond cleavage is involved during hydrolysis. The apparent carbon kinetic isotope effect (AKIEC ) ranged from 1.045 to 1.058. In contrast to hydrolysis, both carbon and hydrogen isotope fractionation were observed during radical oxidation of TBP by OH and SO4 –, yielding εC from −0.9 ± 0.1‰ to −0.5 ± 0.1‰ and εH from −20 ± 2‰ to −11 ± 1‰. AKIEC and AKIEH varied from 1.007 to 1.011 and from 1.594 to 2.174, respectively. The correlation of 2 H and 13 C isotope fractionation revealed Λ values ranging from 17 ± 1 to 25 ± 6. Results demonstrated that the correlation of 2 H and 13 C isotope fractionation of TBP allowed to identify radical reactions and to distinguish them from hydrolysis. The presented dual isotope analysis approach has diagnostic value for characterizing the chemical transformation of TBP in the environment. Highlights: Quantification of 2 H and 13 C isotope enrichment factors of TBP. Comparison of isotope fractionation patterns upon hydrolysis and radical oxidation. Charactering the CO, CH bond cleavage of TBP using apparent kinetic isotope effect.